PsycEXTRA Dataset 2012
DOI: 10.1037/e502412013-184
|View full text |Cite
|
Sign up to set email alerts
|

Amodal Aspects of Linguistic Design

Abstract: All spoken languages encode syllables and constrain their internal structure. But whether these restrictions concern the design of the language system, broadly, or speech, specifically, remains unknown. To address this question, here, we gauge the structure of signed syllables in American Sign Language (ASL). Like spoken languages, signed syllables must exhibit a single sonority/energy peak (i.e., movement). Four experiments examine whether this restriction is enforced by signers and nonsigners. We first show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…One of the substantial discoveries of the last 50 years is that sign languages show all the properties of full natural languages on all relevant levels of linguistic structure, including, for instance, sublexical structure at the phonological level ( Emmorey, 2002 ; Meier et al, 2002 ; Sandler and Lillo-Martin, 2006 ; Channon and van der Hulst, 2011 ; Berent et al, 2013 ). However, it has been suggested that, in conversational turn-taking, signers may show greater toleration for overlap due to the characteristics of the visual modality.…”
Section: Introductionmentioning
confidence: 99%
“…One of the substantial discoveries of the last 50 years is that sign languages show all the properties of full natural languages on all relevant levels of linguistic structure, including, for instance, sublexical structure at the phonological level ( Emmorey, 2002 ; Meier et al, 2002 ; Sandler and Lillo-Martin, 2006 ; Channon and van der Hulst, 2011 ; Berent et al, 2013 ). However, it has been suggested that, in conversational turn-taking, signers may show greater toleration for overlap due to the characteristics of the visual modality.…”
Section: Introductionmentioning
confidence: 99%
“…Son in the vocal (and movement in the signed) modality could thus be instantiations of a module whose modality-unspecific domain is perceptual salience. Berent et al (2013) adduce experimental evidence supporting this amodal view on sonority. Sandler and Lillo-Martin (2006: 235-245) offer an overview of the question.…”
Section: Sonority Is Phonetically Composite and Entropy-drivenmentioning
confidence: 74%
“…She further shows that sonority sequencing does not merely extend to lexical items that speakers have never come across: it is also active in structures that are unattested in the speaker's language, such as branching onset preferences produced by Korean speakers, whose language lacks branching onsets (Berent et al 2008). Finally, as was mentioned in footnote 37, Berent et al (2013) adduce experimental evidence for sonority being in fact amodal, that is, a single system shared by the vocal and signed modalities whose expression is loudness etc. on the former, movement on the latter side.…”
Section: Workings Of Phonology With Three Modulesmentioning
confidence: 91%
“…Other evidence suggests that nonsigners' representation of signs relies not only on visual strategies, but also on shared grammatical constraints. For example, our past research (Berent et al 2013) shows that signers and nonsigners both define signed syllables by the number of sonority peaks (i.e., movement)an amodal principle that likely forms part of universal grammar (UG). Critically, these biases are linguistic, rather than merely visual, as nonsigners selectively apply them to syllables, but not to morphemes (see Fig.…”
Section: Open Peer Commentarymentioning
confidence: 99%